PENGARUH MODEL PEMBELAJARAN GROUP TO GROUP EXCHANGE BERBANTUAN LEMBAR KERJA PESERTA DIDIK TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 1 INDRALAYA - Helen Rahayu; Siti Fatimah; Rusmin AR (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2018)
This study discusses about the effect of learning model of Group To Group with the worksheet of learners on students' learning outcomes on economic subjects in SMA Negeri 1 Indralaya. The formulation of the research problem is